Comparative assessment of efficacy of various anesthesia options after cesarean section - O. V. Ryazanova; Yu. S. Аleksandrovich; Yu. N. Gorokhova (Вестник анестезиологии и реаниматологии)
The article describes the comparative assessment of efficacy of transversus abdominis plane block as a component of multimodal analgesia during cesarean section.Subjects and methods. 165 primiparous women were enrolled into the study, their average age made 30.5 years. Operative delivery was performed under spinal anesthesia. All patients were divided into five groups. In the patients in Groups 1 and 3, postoperative analgesia was performed using transversus abdominis plane (TAP) block without ultrasound guidance, while in Groups 2 and 4, TAP block was guided by ultrasound. In Groups 1 and 2, ropivacaine hydrochloride was used at a concentration of 0.2%, in Groups 3 and 4 - 0.375%. In Group 5, paracetamol in combination with narcotic analgesics was used for analgesia. Pain intensity was assessed every hour using a visual analogue pain scale at rest and during movement during the 1st day after delivery. To assess the severity of the stress response and metabolic status of patients, concentrations of cortisol, prolactin and glucose in blood plasma was tested. The levels of cortisol and prolactin were tested in 4 stages: before surgery, 1 hour after surgery, 6 and 24 hours after delivery. Plasma glucose was tested in 3 stages: before surgery, 1 hour and 6 hours after surgery.Results. TAP block in combination with paracetamol provided adequate postoperative analgesia, reduced the consumption of analgesics, and also contributed to the earliest activation of new mothers after cesarean section. The use of 0.2% ropivacaine hydrochloride solution with TAP block was equally effective as the use of 0.375% solution of ropivacaine hydrochloride. Ultrasound guided TAP block significantly improved the quality of postoperative pain management. TAP block reduced the level of stress hormones in patients but in 24 hours, the levels of stress hormones in all groups of patients receiving and not receiving TAP block did not differ.